2021
DOI: 10.3390/horticulturae7120530
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Effects of Nitrogen Fertilization on Grape Vegetative Growth, Berry Quality and Pest Development in Mediterranean Vineyards

Abstract: Nitrogen is a key macronutrient for the quantitative and qualitative yield of grapes; in addition, it influences the development and reproduction of grape pests. The multiple effects of different nitrogen rates were investigated on the red berry cultivar ‘Carignano’ and the grape pest Planococcus ficus in a two-year field trial. Different amounts of ammonium nitrate were compared: 0, 80 and 160 Units ha−1 for mineral nitrogen. The amount of nitrogen fertilization supplied influenced the nitrogen status of vine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
(69 reference statements)
2
5
0
Order By: Relevance
“…For instance, with regard to fertilization schemes, application of nitrogen fertilization decreased total anthocyanin and sugar contents in cranberry (Jamaly et al, 2021). This was in agreement with the results obtained by Cocco et al (2021) who showed that nitrogen fertilization decreased the anthocyanin content, organic acid content, and sugar content of grapes (Cocco et al, 2021). Similarly, Rupp and Tränkle (2000) reported decreased amount of vitamin C and sugars in redcurrant following excess nitrogen fertilization (Rupp & Tränkle, 2000), while nitrogen, phosphorus, and potassium fertilizations did not produce significant changes in sugar, organic acids, nitrogen, magnesium, and zinc levels in blueberries (Milo sevi c et al., 2018).…”
Section: Plant Nutrition and Fertilizationsupporting
confidence: 90%
“…For instance, with regard to fertilization schemes, application of nitrogen fertilization decreased total anthocyanin and sugar contents in cranberry (Jamaly et al, 2021). This was in agreement with the results obtained by Cocco et al (2021) who showed that nitrogen fertilization decreased the anthocyanin content, organic acid content, and sugar content of grapes (Cocco et al, 2021). Similarly, Rupp and Tränkle (2000) reported decreased amount of vitamin C and sugars in redcurrant following excess nitrogen fertilization (Rupp & Tränkle, 2000), while nitrogen, phosphorus, and potassium fertilizations did not produce significant changes in sugar, organic acids, nitrogen, magnesium, and zinc levels in blueberries (Milo sevi c et al., 2018).…”
Section: Plant Nutrition and Fertilizationsupporting
confidence: 90%
“…Numerous researchers have extensively studied the benefit of nitrogen in grapevine nutrition. The positive influence of nitrogen fertilizing was confirmed by Cocco et al (2021), Delgado et al (2004), Gay-Eynard (2000), etc. According the Cocco et al (2021), nitrogen had a direct and positive effect on grape yield and vine mealybug development, highlighting the importance of integrated crop management and pest control practices to promote grape production.…”
Section: Resultsmentioning
confidence: 85%
“…The highest fruit yield was recorded in T2 (17.25 and 15.51 kg/vine) followed by T9 (16.40 and 14.83 kg/vine) while the lowest fruit yield was recorded in T1 (6.48 and 5.60 kg/vine). The application of nitrogen fertilizer may potentially influence the nitrogen content of the grapevines, which could result in the enlargement of leaf area and an overall boost in grape yield, mainly attributable to the increased cluster weight [12]. Excessive nitrogen supply leads to increased vegetative growth, which can, in turn, compete with the translocation and accumulation of sugars [13] causing a delay in berry ripening and an increased susceptibility to fungal diseases.…”
Section: Resultsmentioning
confidence: 99%